Association between diabetes mellitus and cirrhosis mortality: the Singapore Chinese Health Study. (16th September 2016) - Goh, George Boon‐Bee; Pan, An; Chow, Wan‐Cheng; Yuan, Jian‐Min; Koh, Woon‐Puay
Abstract: Background & Aim: Diabetes mellitus has been linked to cirrhosis‐related mortality in Western populations, but less is known about this relationship in Asian populations. We studied the impact of diabetes on the risk of cirrhosis mortality in a population‐based cohort among Chinese in Singapore. Methods: We used data collected and analysed from the Singapore Chinese Health Study, a prospective community‐based cohort of 63 275 subjects aged 45–74 years during enrolment between 1993 and 1998. Information on diet, lifestyle and medical history was collected via structured questionnaire. Mortality cases from cirrhosis in the cohort were identified via linkage with nationwide death registry up to 31 December 2014. Cox proportional regression models were used to estimate the associations with adjustment for risk factors of cirrhosis. Results: After a mean follow‐up of 16.9 years, there were 133 deaths from cirrhosis. Diabetes was associated with an increased risk of cirrhosis mortality (hazard ratio [HR]: 2.80; 95% confidence interval [CI]: 2.04–3.83), and for both viral (HR: 2.20; 95% CI: 1.18–4.11) and non‐viral hepatitis‐related cirrhosis mortality (HR: 3.06; 95% CI: 2.13–4.41). The association between diabetes and non‐viral hepatitis‐related cirrhosis mortality was stronger among participants of body mass index (BMI) less than 23 kg/m 2 (HR: 7.11; 95% CI: 3.42–14.79) compared to heavier individuals (HR: 2.28; 95% CI: 1.20–4.35) ( P interaction =0.02). Conclusion: Diabetes is a risk factor for cirrhosis mortality, especially for non‐viral hepatitis‐related cirrhosis in population with BMI considered low or normal in Asia.